Cosmic Ray Neutron Sensing: Estimation of Agricultural Crop Biomass Water Equivalent - Wahbi, Ammar (Springer Nature, 2018)
Earth Science; Soil Management; Water Management; Crop Nutrition; Nuclear; CRNS; Biomass Water Equivalent; Remote Sensing; Satellite Imagery